Wastewater antibody signatures reflect SARS-CoV-2 infection and immunization patterns in the population - Dhammika Leshan Wannigama; Mohan Amarasiri; Phatthranit Phattharapornjaroen; Cameron Hurst; Charin Modchang; John Giles; Jillian Gauld; Tanakorn Chantanasaro; Kazuhiko Miyanaga; Longzhu Cui; Stefan Fernandez; Hirotake Mori; et al. (Water Research, 2026)

Predictions of New Horizons’ termination shock crossing - Jonathan Gasser; Justyna M. Sokół; Heather A. Elliott; Maher A. Dayeh; Kelsi N. Singer; S. Alan Stern; Igor Baliukin; Sergey Korolkov; Pontus C. Brandt; Joel W. Parker; Andrew R. Poppe; Anne J. Verbiscer; et al. (Advances in Space Research, 2026)

Habitat use differences mediate population threat exposure in white sturgeon - Jonathan A. Walter; Gabriel P. Singer; Daniel C. Reuman; Scott F. Colborne; Lawrence W. Sheppard; Daniel R. O’Donnell; Nat Coombs; Erin E. Tracy; Myfanwy Johnston; Emily A. Miller; Anna E. Steel; John T. Kelly; et al. (Environmental Biology of Fishes, 2026)

Presence of emerging organic contaminants and microbial indicators in surface water and groundwater in urban India - Bentje Brauns; Subhash Chandra; Wayne Civil; Dan J. Lapworth; Alan M. MacDonald; Andrew A. McKenzie; Daniel S. Read; Muddu Sekhar; Andrew C. Singer; Amritha Thankachan; Holly J. Tipper (Environmental Pollution, 2024)

A critical meta-analysis of predicted no effect concentrations for antimicrobial resistance selection in the environment - Aimee K. Murray; Isobel C. Stanton; Holly J. Tipper; Helen Wilkinson; Wiebke Schmidt; Alwyn Hart; Andrew C. Singer; William H. Gaze (Water Research, 2024)

Do storm overflows influence AMR in the environment and is this relevant to human health? A UK perspective on a global issue - Holly J. Tipper; Isobel C. Stanton; Rachel A. Payne; Daniel S. Read; Andrew C. Singer (Water Research, 2024)

High throughput qPCR unveils shared antibiotic resistance genes in tropical wastewater and river water - Thitima Srathongneam; Montakarn Sresung; Phongsawat Paisantham; Pacharaporn Ruksakul; Andrew C. Singer; Rojana Sukchawalit; Jutamaad Satayavivad; Skorn Mongkolsuk; Kwanrawee Sirikanchana (Science of The Total Environment, 2024)

Diurnal changes in pathogenic and indicator virus concentrations in wastewater - Kata Farkas; Igor Pântea; Nick Woodhall; Denis Williams; Kathryn Lambert-Slosarska; Rachel C. Williams; Jasmine M. S. Grimsley; Andrew C. Singer; Davey L. Jones (Environmental Science and Pollution Research, 2023)
Wastewater-based epidemiology (WBE) has been commonly used for monitoring SARS-CoV-2 outbreaks. As sampling times and methods (i.e. grab vs composite) may vary, diurnal changes of viral concentrations in sewage should be better understood. In this study, we collected untreated wastewater samples hourly for 4 days at two wastewater treatment plants in Wales to establish diurnal patterns in virus concentrations and the physico-chemical properties of the water. Simultaneously, we also trialled three absorbent materials as passive samples as a simple and cost-efficient alternative for the collection of composite samples. Ninety-six percent of all liquid samples ( n = 74) and 88% of the passive samplers ( n = 59) were positive for SARS-CoV-2, whereas 87% and 97% of the liquid and passive samples were positive for the faecal indicator virus crAssphage, respectively. We found no significant daily variations in the concentration of the target viruses, ammonium and orthophosphate, and the pH and electrical conductivity levels were also stable. Weak positive correlations were found between some physico-chemical properties and viral concentrations. More variation was observed in samples taken from the influent stream as opposed to those taken from the influent tank. Of the absorbent materials trialled as passive samples, we found that tampons provided higher viral recoveries than electronegative filter paper and cotton gauze swabs. For all materials tested, viral recovery was dependent on the virus type. Our results indicate that grab samples may provide representative alternatives to 24-h composite samples if taken from the influent tank, hence reducing the costs of sampling for WBE programmes. Tampons are also viable alternatives for cost-efficient sampling; however, viral recovery should be optimised prior to use.

Equal use of Indigenous and scientific knowledge in species assessments: A case study from the Northwest Territories, Canada - Claire L. Singer; Mélanie R. Routh; Michele J. Grabke; Leon Andrew; Suzanne Carrière; Aimee Guile; Alestine Andre; Allison Thompson; Deborah Simmons; Kaytlin Cooper; Lynda Yonge; Moise Rabesca; et al. (Biological Conservation, 2023)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Genetic resistance to diet-induced obesity in chromosome substitution strains of mice - Lindsay C. Burrage; Annie E. Baskin-Hill; David S. Sinasac; Jonathan B. Singer; Colleen M. Croniger; Andrew Kirby; E. J. Kulbokas; Mark J. Daly; Eric S. Lander; Karl W. Broman; Joseph H. Nadeau (Mammalian Genome, 2010)

Characterizing the regulation of the Pu promoter in Acinetobacter baylyi ADP1 - Wei E. Huang; Andrew C. Singer; Andrew J. Spiers; Gail M. Preston; Andrew S. Whiteley (Environmental Microbiology, 2008)
Summary Effective gene trapping and screening requires sensory and regulatory compatibility of both host and exogenous systems. The naturally competent bacterium Acinetobacter baylyi ADP1 is able to efficiently take up and integrate exogenous DNA into the chromosome, making it an attractive host system for a wide range of metagenomic applications. To test the ability of A. baylyi ADP1 to express the XylR‐regulated Pu promoter from Pseudomonas putida mt‐2, we have constructed and examined an A. baylyi ADP1 strain, ADPWH‐ Pu‐lux‐xylR . The Pu promoter in ADPWH‐ Pu‐lux‐xylR was specifically induced by toluene, m ‐, p ‐ and o‐ xylene. The substrate‐induced Pu promoter was highly dependent on the growth medium: it was repressed in rich media until stationary phase, but was immediately induced in minimal medium with glucose as the sole carbon source (MMG). However, the Pu promoter was repressed in MMG when it was supplemented with 5 g l −1 yeast extract. Further investigation showed that the Pu promoter in MMG was repressed by 0.5 g l −1 aspartic acid or asparagine, but not repressed by glutamine. Changing the carbon/nitrogen ratios by addition of ammonia did not significantly affect the Pu promoter activity but addition of nitrate did. These results show that A. baylyi ADP1 reproduced characteristics of the XylR‐regulated Pu promoter observed in its original host. It demonstrates that A. baylyi could provide an excellent genetic host for a wide range of functional metagenomic applications.

Chromosomally located gene fusions constructed in Acinetobacter sp. ADP1 for the detection of salicylate - Wei E. Huang; Hui Wang; Hongjun Zheng; Linfeng Huang; Andrew C. Singer; Ian Thompson; Andrew S. Whiteley (Environmental Microbiology, 2005)
Summary Acinetobacter sp. ADP1 is a common soil‐associated bacterium with high natural competency, allowing it to efficiently integrate foreign DNA fragments into its chromosome. This property was exploited to engineer salicylate‐inducible luxCDABE and green fluorescent protein (GFP) variants of Acinetobacter sp. ADP1. Specifically, Acinetobacter sp. ADPWH _lux displayed the higher sensitivity when comparing the two variants (minimum detection c . 0.5–1 µM salicylate) and a faster turnover of the lux marker gene, making it suitable for whole‐cell luminescence assays of salicylate concentration. In contrast, the longer maturation and turnover times of the GFP protein make the Acinetobacter sp. ADPWH _gfp variant more suited to applications involving whole‐cell imaging of the presence of salicylate. The sensitivity of the luxCDABE variant was demonstrated by assaying salicylate production in naphthalene‐degrading cultures. Assays using ADPWH _lux specifically mapped the kinetics of salicylate production from naphthalene and were similar to that observed by high‐performance liquid chromatography (HPLC) data. However, ADPWH _lux exhibited the higher sensitivity, when compared with HPLC, for detecting salicylate production during the first 24 h of naphthalene metabolism. These data demonstrate that the engineered Acinetobacter variants have significant potential for salicylate detection strategies in laboratory and field studies, especially in scenarios where genetic stability of the construct is required for in situ monitoring.

Bioaugmentation for bioremediation: the challenge of strain selection - Ian P. Thompson; Christopher J. Van Der Gast; Lena Ciric; Andrew C. Singer (Environmental Microbiology, 2005)
Summary Despite its long‐term use in bioremediation, bioaugmentation of contaminated sites with microbial cells continues to be a source of controversy within environmental microbiology. This largely results from its notoriously unreliable performance record. In this article, we argue that the unpredictable nature of the approach comes from the initial strain selection step. Up until now, this has been dictated by the search for catabolically competent microorganisms, with little or no consideration given to other essential features that are required to be functionally active and persistent in target habitats. We describe how technical advances in molecular biology and analytical chemistry, now enable assessments of the functional diversity and spatial distribution of microbial communities to be made in situ . These advances now enable microbial populations, targeted for exploitation, to be differentiated to the cell level, an advance that is bound to improve microbial selection and exploitation. We argue that this information‐based approach is already proving to be more effective than the traditional ‘black‐box’ approach of strain selection. The future perspectives and opportunities for improving selection of effective microbial strains for bioaugmentation are also discussed.